2017
DOI: 10.1093/milmed/usx004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Dirty Dozen: A Proposed Methodology for Assessing Future Bioweapon Threats

Abstract: Our study was designed to provide a concise and east-to-apply set of criteria that could be used by NATO nations to evaluate emerging infectious disease threats with respect to their weaponization potential. Our results were unexpected. We believe that a lack of appropriate weighting factors may explain these results and suggest that future studies weigh each of the 12 proposed criteria based on the intended use of the assessment data and other situational factors. We believe that the greatest value of our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Ricin toxin (RT) is considered a high priority biothreat agent by the Centers for Disease Control and Prevention (CDC), the US Department of Defense (DOD), and the North Atlantic Treaty Organization (NATO) due to its accessibility, stability, and high toxicity, especially by the aerosol route (1,2). In nonhuman primates (NHPs), inhalation of RT elicits the clinical equivalent of acute respiratory distress syndrome (ARDS), characterized by widespread apoptosis of alveolar macrophages, intraalveolar edema, neutrophilic infiltration, accumulation of proinflammatory cytokines, and fibrinous exudate (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Ricin toxin (RT) is considered a high priority biothreat agent by the Centers for Disease Control and Prevention (CDC), the US Department of Defense (DOD), and the North Atlantic Treaty Organization (NATO) due to its accessibility, stability, and high toxicity, especially by the aerosol route (1,2). In nonhuman primates (NHPs), inhalation of RT elicits the clinical equivalent of acute respiratory distress syndrome (ARDS), characterized by widespread apoptosis of alveolar macrophages, intraalveolar edema, neutrophilic infiltration, accumulation of proinflammatory cytokines, and fibrinous exudate (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Ricin toxin has been classified as a biological threat agent by the Centers for Disease Control and Prevention because of its extreme toxicity, the ease by which it can be procured from castor beans, and the absence of any available countermeasures . Continued concerns about ricin are underscored by a recent NATO Biomedical Advisory Council report that ranked ricin at the top of its list of agents with weaponization potential . Ricin is a ∼65 kDa heterodimeric glycoprotein consisting of 2 subunits, RTA and RTB, which are joined via a single disulfide bond.…”
Section: Introductionmentioning
confidence: 99%
“…NATO’s Biomedical Advisory Council recently concluded that ricin ranks at the top of the list of potential biothreat agents, due in large part to the toxin’s extreme potency against numerous different cell types, as well as its capacity to be disseminated via aerosol 1 . In rodents, swine, and non-human primates (NHPs), inhalational ricin exposure evokes what is clinically equilavent to acute respiratory distress syndrome (ARDS) 24 In rodents and NHPs, the lethal dose 50 (LD 50 ) of ricin by aerosol is ~4 μg/kg 57 The hallmarks of ricin-induced lung damage include early onset of alveolar macrophage apoptosis (6-12 h) followed hours later by intra-alveolar edema, accumulation of inflammatory cytokines in the BAL, neutrophilic infiltration, and fibrinous exudate 5, 7–10 .…”
Section: Introductionmentioning
confidence: 99%